2020
DOI: 10.3389/fpls.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Excess Pyrophosphate Restrains Pavement Cell Morphogenesis and Alters Organ Flatness in Arabidopsis thaliana

Abstract: cotyledon proximo-distal and medio-lateral phenotypic quantification implicated restricted cotyledon expansion along the medio-lateral axis in the crinkled surface of an-1 fugu5-1. Together, our data suggest that PPi homeostasis is a prerequisite for proper pavement cell morphogenesis, epidermal growth and development, and organ flattening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 53 publications
(103 reference statements)
3
35
0
Order By: Relevance
“…We reported that excess PPi in the H + -PPase loss-of-function fugu5 mutant severely compromises gluconeogenesis from seed storage lipids and inhibits a hypocotyl elongation in etiolated seedlings ( Ferjani et al, 2011 , 2014a , 2018 ), arrests cell division in cotyledonary palisade tissue, and triggers a compensated cell enlargement (CCE; Tsukaya, 2002 , 2008 ; Horiguchi et al, 2005 , 2006a , b ; Ferjani et al, 2007 , 2008 , 2010 , 2011 , 2013a , b ; Amano et al, 2015 ; Katano et al, 2016 ; Takahashi et al, 2017 ; Tabeta et al, 2021 ; Nakayama et al, 2022 ). It is important to note that these phenotypes were recovered by exogenous sucrose (Suc) supply or specific removal of PPi from the fugu5 background by the yeast cytosolic PPase IPP1 under the control of the vacuolar H + -pyrophosphatase AVP1 / FUGU5 promoter in fugu5-1 AVP1 pro ::IPP1 transgenic lines ( Ferjani et al, 2011 , 2014a , b ; Asaoka et al, 2019 ; Gunji et al, 2020 ). Consistently, CE-TOF MS analyses of the major metabolites characteristic of gluconeogenesis from seed storage lipids identify UGPase as the major target of the inhibitory effects of excess PPi in planta ( Ferjani et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that excess PPi in the H + -PPase loss-of-function fugu5 mutant severely compromises gluconeogenesis from seed storage lipids and inhibits a hypocotyl elongation in etiolated seedlings ( Ferjani et al, 2011 , 2014a , 2018 ), arrests cell division in cotyledonary palisade tissue, and triggers a compensated cell enlargement (CCE; Tsukaya, 2002 , 2008 ; Horiguchi et al, 2005 , 2006a , b ; Ferjani et al, 2007 , 2008 , 2010 , 2011 , 2013a , b ; Amano et al, 2015 ; Katano et al, 2016 ; Takahashi et al, 2017 ; Tabeta et al, 2021 ; Nakayama et al, 2022 ). It is important to note that these phenotypes were recovered by exogenous sucrose (Suc) supply or specific removal of PPi from the fugu5 background by the yeast cytosolic PPase IPP1 under the control of the vacuolar H + -pyrophosphatase AVP1 / FUGU5 promoter in fugu5-1 AVP1 pro ::IPP1 transgenic lines ( Ferjani et al, 2011 , 2014a , b ; Asaoka et al, 2019 ; Gunji et al, 2020 ). Consistently, CE-TOF MS analyses of the major metabolites characteristic of gluconeogenesis from seed storage lipids identify UGPase as the major target of the inhibitory effects of excess PPi in planta ( Ferjani et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the outermost cotyledon layer in fugu5 revealed an increase in stomatal density (i.e., the number of stomata per unit area) in violation of the one-cell-spacing rule, a defect in stomata closure ( Asaoka et al, 2019 ), and showed that pavement cells (PCs) exhibit defective puzzle-cell formation ( Gunji et al, 2020 ). It is important to note that specific removal of PPi in fugu5-1 AVP1 pro ::IPP1 transgenic lines restored these epidermal phenotypic aberrations in the fugu5 background ( Gunji et al, 2020 ). Furthermore, in fugu5 GC1 pro ::IPP1 transgenic lines, which exclusively express IPP1 in guard cells, stomatal closure recovered, which suggests a role for H + -PPase in stomatal function ( Asaoka et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we developed a framework to capture and analyze 4D information of cotyledon pavement cell growth and morphogenesis. We believe that this framework should aid analysis of mutant phenotypes, especially in the 3D deformation of the cotyledon surface, as recently reported by Gunji et al 2020. Additionally, our accurate and high-throughput acquisition of growing cell structures might be suitable for use in making an in silico model cell structure, which is generated by the observed data.…”
Section: Resultsmentioning
confidence: 57%
“…To detect morphological differences in pavement cells of 20day-old leaves, SEM analysis was performed. Pavement cells usually exhibit puzzle-cell formation, but very recently Gunji et al (2020) reported that the complexity of cotyledon pavement cells was reduced by PPi accumulation via inhibiting microtubule dynamics. On both MGRL and MGRL Am , WT leaves showed normal pavement cell structure ( Figures 2F,G).…”
Section: Morphological Phenotypes Of Leaf Of Fugu5mentioning
confidence: 99%
“…A T-DNA insertion H + -PPase knockout mutant vhp1-1 of Arabidopsis thaliana (A. thaliana) and amino acid exchange and deletion mutants of H + -PPase (fugu5s) showed abnormal cotyledon shape, with fewer and larger cells, when seedlings were grown in the absence of sucrose (Ferjani et al, 2011), as well as a mild suppression of plant growth (Asaoka et al, 2016), and delayed stomatal closure (Asaoka et al, 2019). Very recently, excess PPi has been reported to limit cotyledon pavement cell morphogenesis and to alter cotyledon flatness (Gunji et al, 2020). On the contrary, V-ATPase knockout mutant vha-a2 vha-a3 showed severer growth defect and higher vacuolar pH than fugu5, suggesting that V-ATPase is the primary vacuolar proton pump (Krebs et al, 2010;Kriegel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%